2021
DOI: 10.1186/s10195-021-00583-x
|View full text |Cite
|
Sign up to set email alerts
|

Low rate of early periprosthetic fractures in cementless short-stem total hip arthroplasty using a minimally invasive anterolateral approach

Abstract: Purpose Minimally invasive (MIS) approaches in combination with short stems have gained popularity in recent years in total hip arthroplasty (THA). A decreased risk for periprosthetic femoral fractures (PFFs) is reported for cementless short-stem THA, but in contrast to other approaches, the risk factors for PFFs for short-stem THA using MIS anterolateral approach in supine position are not described in literature. Methods A single-center consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(59 reference statements)
3
1
0
Order By: Relevance
“…We could not confirm this finding, since we only found one periprosthetic fracture in the non-obese patient group at the 5-year follow-up. This is in line with a study of Luger et al, in which BMI was not a risk factor for periprosthetic fractures in short stem THA [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We could not confirm this finding, since we only found one periprosthetic fracture in the non-obese patient group at the 5-year follow-up. This is in line with a study of Luger et al, in which BMI was not a risk factor for periprosthetic fractures in short stem THA [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, this can increase the heterogeneity of our study cohort, since patients’ activity levels can differ with age. Nevertheless, the mean age of both cohorts is comparable with other studies investigating the effect of obesity in short stem THA [ 33 , 34 , 36 ]. In addition, the multicenter study design can decrease the homogeneity of the study cohort because of different acetabular cups used and different surgeons who performed the implantation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Dietrich et al [ 44 ] reported a significantly reduced fracture rate of 1.6% vs 6.8% in 457 DAA with conventional straight stems. Luger et al [ 45 ] reported 0.9% of intraoperative fractures after 1052 DAA- THA with the same straight stem used in our study. In our opinion, the use of short stems with specific instruments for DAA favors the introduction into the femoral canal, decreases the points of conflict with cortices during introduction and decreases the incidence of complications.…”
Section: Discussionsupporting
confidence: 63%
“…When patients are operated on through DAA, intra-operative femoral fractures and implant malpositioning could occur because of the impingement of the surgical instruments against the adipose tissue [14,16,30]. In order to reduce periprosthetic fracture, specific short stems seem to reduce the risk; in addition, dedicated off-set instrumentation is required to permit a suitable placement of implants without force [31]. Russo et al [14] reported an increased rate of infectious complications in patients with BMI over 30 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%